Effects of high-intensity training with one versus three changes of direction on youth female basketball players` performance - Sanchez-Sanchez, J.; Carretero, M.; Ramirez-Campillo, R.; Petisco, C.; Diego, M.; Gonzalo-Skok, O.; Nakamura, F. Y. (Kinesiology, 2018)
To compare the effects of high-intensity interval training (HIT) with one versus three changes of direction (COD) on young (age, 17.2±1.1 years) female basketball players` performance, six weeks of regular basketball training (control period) was followed by six weeks of high-intensity training added to regular training , two times per week, with a random allocation of athletes to either HIT with one (HIT-COD1; n=6) or three COD (HIT-COD3; n=6). Before and after the control and HIT-COD training periods athletes performed repeatedsprint ability test (RSA), modified agility T-test (MAT), V-cut, triple standing dominant (TS-D) and nondominant (TS-ND) jump, TS-D and TS-ND with COD tests, and 30-15 Intermittent Fitness Test (30-15IFT). With the exception of a substantial improvement in V-cut in both groups, no substantial changes occurred during the control period. Both HIT-COD training programs improved V-cut, although only HIT-COD3 substantially improved RSA mean time (RSAm), MAT and the final speed reached in 30-15IFT (VIFT). The between-group comparison revealed greater improvements in RSAm and VIFT in HIT-COD3 than in HITCOD1. In conclusion, supplementation of basketball training with HIT-COD drills adds improvements to young female basketball player`s performance, especially when 3 COD are incorporated into HIT.